Transposition of a pancreas transplant from the bladder to the terminal ileum twenty years after combined allogenic kidney-pancreas-transplantation. (November 2017) - Stula, Astrid; Maier, Tanja; Heverhagen, Anna; Geks, Josef
Abstract : Introduction: During the first years of combined allogenic kidney-pancreas-transplantation bladder diversion of the exocrine pancreas secretion was used. After reporting urological and systemic complications it was switched to an enteric diversion with excellent results of pancreas function. Today enteric diversion of the pancreatic ductal secretion is the standard procedure. Nevertheless there are still patients alive with bladder diversion from the early years of transplantation with a good pancreatic function but loss of kidney function. This case describes such a patient and how we dealt with the problem. Case description: A 53-year old male patient presented with a progressive renal failure twenty years after combined allogenic kidney-pancreas-transplantation with bladder diversion of the exocrine pancreas secretions. Urine excretion was declining with a pre-dialysis renal failure. Still the pancreas transplant was working properly without the need of insulin therapy. We therefore carried out a separation of the graft duodeno-cystostomy and re-established diversion by a side-to-side graft duodenal-recipient ileal anastomosis. This was done by a 2-layer hand sewn technique. Bladder catheter, drainage near the bladder and drainage near the anastomosis were removed after 5, 8 and 10 days respectively. The pancreas showed proper function without the need of insulin therapy. The patient was released from hospital 14 days after the operation. Results and Conclusions: Transposition of a pancreas transplant from the bladder to the terminal ileum twenty years after primary transplantation is technically possible. In this case it was also reasonable in order to protect the bladder from the aggressive pancreatic ductal secretion. Because of the declining urine excretion due to progressive failure of the kidney transplant the exocrine secretion was not properly diluted anymore with the risk of hematuria, lower urinary tract infections, reflux-associated pancreatitis and transitional cell dysplasia. These conditions could limit the opportunity for the patient for a second kidney donation. Take home message: Transposition of a pancreas transplant from the bladder to the terminal ileum twenty years after primary transplantation is technically possible and reasonable to offer the patient a chance for a second kidney donation.